Small Group Acivities for Pallet Cover Design Plan - Rahayu, Siti; Wiyatno, Tri Ngudi; Zavero, Chicko Al (Proceeding International Pelita Bangsa, 2023)
This paper examines the utilization of the Small Group Activity (SGA) method using in manufacuring company as an example. The topic was selected due to issues identified by the company in the domain of quality management. The aim of the investigation is to provide theoretical concepts for the enhancement of group activities and their impact on organizational effectiveness. Methods of Continuous Improvement in the Philosophy of Kaizen (SGA) and a Presentation of the Practical Benefits of Its Implementation. The results indicate that it could be a highly effective method in solving problems and improving. Design and manufacture special pallet racks for Cover components. The elimination of non-value added (NVA) activities in the cover component setting process. Components received from suppliers can either be stored or directly allocated to production. Loading components from suppliers maximizes efficiency as it takes up minimal space and there will no longer be a build-up of waste from strapping plates after the setting process.